Tingkat Kecemasan Siswa yang Mempunyai Orang Tua Tunggal dalam Menghadapi Ujian - Irene Cosmalinda Agatha (STIKes Patria Husada Blitar, 2016)
Anxiety is the narrowing of the field of perception but still may be directed to others. This study aimed to identify the anxiety levels of students who have single parents in the exam. Method: Descriptive research design. The population was 31 students who have single parents. The sample was 31 students. The Sampling technique was total sampling. The Instrument used Hars questionnaires. Result: The results showed that 87% students experiencing anxiety in susceptible adaptive anxiety which makes the child’s motivation to achieve the goal. Based on the results, there were three things that stand out, namely the onset of anxiety disorders of sleep (not sleep soundly) 30%, impaired intelligence (poor memory, difficulty concentrating) 26%, and anxiety (a bad feeling before the exam) 17%. Discussion: It was expected that counseling can determine the level of anxiety felt by the class XII students who have single parents and allows students to uncover the feelings of the problem so that the learning process will increase.